The African context of business and society - Obi Omeihe, Kingsley; Harrison, Christian (Emerald Publishing Limited, 2022)
The African Context of Business and Society traces the unique and often overlooked and unestimated contours of African business and society, abandoning the flawed assumption that western preconceptions can be directly transplanted- one that has often led to incorrect macro-theorisations. Africa's diverse economy has been influenced by historical and cultural change, and The African Context of Business and Society's novel indigenous viewpoints address topics such as female entrepreneurship, organizational culture, the role of religion on employee trust, authentic leadership and more. Understanding individual and organisational behaviour, the chapters examine the under-researched aspects of Africa's business and society and both opportunities and constraints. The New Frontiers in African Business and Society series provides innovative reflections on the nature of business and society across parts of Africa and its emerging economy. Distinguished scholars formulate important answers to the problems within the continent, discovering new avenues of research and pathways forward.
Keywords: Business enterprises -- Africa.; Entrepreneurship -- Africa.; Africa -- Economic conditions -- 1960-; Africa -- Social conditions -- 1960-; Business & Economics -- Development -- Sustainable Development.; Business strategy.; elektronické knihy; electronic books